Eficacia de diferentes aceites esenciales en la aromaterapia para el control de la ansiedad dental en niños: Revisión de literatura - Flores Culqui, Stephanie Katherina (2025)
Objective: The objective of this study was to perform a literature review on the effectiveness of essential oils in aromatherapy for the control of dental anxiety in children Material and methods: A comprehensive search was conducted in the databases of Cochrane Library, EBSCO, EMBASE, Pubmed, Science Direct and Scopus where articles 10 years old between 2014 and 2025 were included. The descriptors used were “dental anxiety”, “aromatherapy”; “dentistry”, “child”; “essential oils” and “pediatric dentistry”. Articles that met the inclusion and exclusion criteria were included. Results: A An initial bibliographic search yielded 1577 studies, after eliminating duplicates and discarding articles reviewed by their abstract and totality, 18 studies were eligible. Based on the selected studies, the most effective essential oil was lavender, followed by chamomile and orange. Compared to the negative control condition, aromatherapy might reduce the anxiety-related physiological parameters and psychometric rating, and there might be no intergroup difference when compared with music and conscious sedation. However, it is more effective when compared to the show-tell-do, audiovisual and gustatory distraction techniques. Conclusion: The use of aromatherapy is an effective, simple, low-risk, and low-cost non-pharmacological method for reducing dental anxiety in pediatric patients.